Efektivitas Model Pembelajaran Problem Based Learning (PBL) Berbantuan Media Pop Up Book Pada Pelajaran Bahasa Indonesia Untuk Meningkatkan Kemampuan Literasi Bagi Siswa Kelas 3 SD Negeri Panjang 03 Kecamatan Ambarawa Kabupaten Semarang. - Kristia Setyaningsih; Agus Sutono; Dini Rakhmawati (LPPM Undiksha, 2025)
This research is motivated by students' low literacy skills in Indonesian language learning, as indicated by their inability to understand texts, express ideas in writing, and low interest in reading. The purpose of this study is to determine the effectiveness of the Problem-Based Learning Model Assisted by Pop Up Book Media in Indonesian Language Lessons to Improve Literacy Skills for 3rd Grade Elementary School Students. This study employs a quantitative, experimental approach. The research sample consists of Class 3A students, the experimental class, with a total of 27 students, and Class 3B, the control class, with a total of 27 students. The experimental design in this study begins with a pretest and ends with a posttest. The instrument used for data collection is an observation sheet in checklist form. The application of the Problem-Based Learning (PBL) model, assisted by pop-up book media, is effective in improving students' literacy skills in Indonesian language learning. Improvements are seen in the ability to understand reading, write ideas coherently, and in increased student interest and activity during the learning process. In conclusion, the Problem-Based Learning (PBL) model, supported by pop-up books, has proven effective in improving students' literacy skills in Indonesian language learning. The theoretical implications of this research strengthen and enrich scientific research on constructivist theory, modern literacy theory, and the development of innovative learning models.